Developmental DNA methyltransferase expression in the fire ant Solenopsis invicta. (16th January 2017) - Kay, Sasha; Skowronski, Daniel; Hunt, Brendan G.
Abstract: DNA methylation is accomplished in animals by 2 classes of enzymes known as DNA methyltransferases, DNMT3 and DNMT1, which perform de novo methylation and maintenance methylation, respectively. Several studies of hymenopteran eusocial insects suggest that DNA methylation is capable of influencing developmental plasticity. However, fundamental questions remain about the patterning of DNA methylation during the course of insect development. In this study, we performed quantitative real‐time PCR (qPCR) on transcripts from the single‐copy orthologs of DNMT1 and DNMT3 in the red imported fire ant, Solenopsis invicta . In particular, we assessed the expression of S. invicta Dnmt1 and Dnmt3 mRNA during 7 stages of worker development, among behaviorally distinct adults, and among male and female gonads. Dnmt3 was most highly expressed during embryonic development, whereas Dnmt1 was similarly expressed throughout the course of development. Moreover, Dnmt1 and Dnmt3 were highly expressed in testes and ovaries. Neither Dnmt was significantly differentially expressed among heads of behaviorally distinct adult castes. Our results support the hypothesis that extensive patterning of DNA methylation occurs during gametogenesis and embryogenesis in the insect order Hymenoptera.